Characteristics of Vacuum Freeze Drying with Utilization of Internal Cooling and Condenser Waste Heat for Sublimation - Alhamid, Muhammad Idrus; Yusuf, Nasruddin; Mahlia, Indra Teuku Meurah; Kosasih, Engkos Ahmad; Yulianto, Muhamad; Ricardi, Rio (Makara Journal of Technology, 2013)
Vacuum freeze drying is an excellent drying method, but it is very energy-intensive because a relatively long drying time is required. This research investigates the utilization of condenser waste heat for sublimation as a way of accelerating the drying rate. In addition, it also investigates the effect of internal cooling combined with vacuum cooling in the pressure reduction process. Jelly fish tentacles were used as the specimen, with different configurations for condenser heat waste and internal cooling valve opening. The results show that heating with condenser heat waste can accelerate the drying rate up to 0.0035 kg/m2.s. In addition, pre-freezing by internal cooling prevents evaporation until the mass of the specimen is 0.47 g and promotes transition of the specimen into the solid phase.